2019
DOI: 10.1021/acs.joc.9b02384
|View full text |Cite
|
Sign up to set email alerts
|

Reagent-Controlled Divergent Synthesis of 2-Amino-1,3-Benzoxazines and 2-Amino-1,3-Benzothiazines

Abstract: A reagent-controlled chemoselective process has been devised for the synthesis of 4H-1,3-benzoxazines and related biologically important heterocycles in high yields under mild conditions. These scaffolds could be efficiently constructed using two different chemoselective reactions that rely on the choice of reagents and reaction conditions. The treatment of various 2-amino-arylalkyl alcohols with isothiocyanates afforded thiourea intermediates, which were reacted in situ with molecular iodine in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…In contrast, structurally enthralling 3‐thia‐1‐azaspiro compounds are barely explored, albeit their medicinal importance [7] . In continuation of our research in this area, [2f] here we have reported P(NMe 2 ) 3 ‐mediated annulation reactions of bis‐nucleophiles and isothiocyanates towards the preparation of diversified N , S ‐heterocycles (Scheme 1).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In contrast, structurally enthralling 3‐thia‐1‐azaspiro compounds are barely explored, albeit their medicinal importance [7] . In continuation of our research in this area, [2f] here we have reported P(NMe 2 ) 3 ‐mediated annulation reactions of bis‐nucleophiles and isothiocyanates towards the preparation of diversified N , S ‐heterocycles (Scheme 1).…”
Section: Introductionmentioning
confidence: 70%
“…N ‐(8‐methyl‐4 H ‐benzo[ d ][1,3]thiazin‐2‐yl)benzamide ( 6 ca ) [2f] (Scheme 4): Off‐white solid ; R f =0.60 (SiO 2 , Hexane/EtOAc=8:2); purification system : CombiFlash MPLC (Hexane/EtOAc=80:20); yield : 251 mg (89%); m.p =128.0–129.2 °C (Lit [2f] 127–128 °C); 1 H NMR (400 MHz, DMSO‐ d 6 ) δ=11.59 (br, 1H), 8.02 (d, J =5.6 Hz, 2H), 7.59 (t, J =7.2 Hz, 1H), 7.49 (t, J =7.5 Hz, 2H), 7.17–7.14 (m, 1H), 7.05 (d, J =4.9 Hz, 2H), 3.93 (s, 2H), 2.31 (s, 3H) ppm; 13 C NMR (100 MHz, DMSO‐ d 6 ) δ=170.1 (less intense), 138.7 (less intense), 134.5 (less intense), 132.81, 129.97, 129.13, 128.79, 125.75, 124.98, 28.82, 17.74 ppm; MS (APCI): [M+1] + =283.1 (99.10%); HRMS (ESI‐QTOF, [M+H] + ): calculated for C 16 H 15 N 2 OS: 283.0905; found: 283.0902.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzoxazine and its derivatives are important scaffolds in biologically active molecules such as pharmaceuticals and agrochemicals (Figure 1). 1 Previous methods for the synthesis of the benzoxazines include the cyclization of thioureas mediated by 1,3-dicyclohexylcarbodiimide (DCC), 2 and starting from isothiocyanates, hypervalentiodine(III)-mediated desulfurative cyclization, 3 cyclization using 1,1′-(ethane-1,2-diyl)dipyridinium bistribromide (EDPBT) as a brominating reagent, 4 cyclodesulfurization with triphenylbismuth dichloride, 5 a Cu 2 O/TBAB-promoted approach in water, 6 and cyclization mediated by stoichiometric iodine in the presence of a base 7 (Scheme 1). However, these methods suffer from harsh reaction conditions, moderate yields, and the use of expensive and/or stoichiometric amounts of reagents.…”
Section: Catalytic Desulfurative Cyclizationmentioning
confidence: 99%
“…[9a] The reaction of 5 with 4nitrophenyl chloroformate and a following base treatment afforded benzoxazinone 7 in 90 % yield and 93 % ee. [22] Moreover, subjecting 5 to ethyl isothiocyanate then iodine provided benzofused heterocycle 8, [23] an analogue of the anticonvulsant drug etifoxine. It is worth mentioning that all these transformations proceeded without any erosion of the enantiopurity.…”
mentioning
confidence: 99%